Factors that influencing the practice of Wasiyyah among Malays in Marang, Terengganu / Norizzati Yasim - Yasim, Norizzati (Faculty of Business Management, University Teknologi MARA, 2018)
Wasiyyah is one of alternative mechanism in Muslim asset management as a preparation for their death by leaving a will for the beloved person. One of the ways of preparing is to write a will that follow the Syariah principle. Wasiyyah can be considered as a gift of the entire asset to the person that does not have blood relationship with decrease person such as adopted child and its allow to be done before the of Faraid- Only one of three of the entire asset can be gift to unrelated person. Based on previous study, Malay society in Malaysia does not take seriously about the estate planning (Ab. Aziz, Nooh, Khairi, Johari, & Iskandar Mirza, 2014). The issue is low awa•eness among society to writing Wasiyyah before their death. Besides, the society more depend on system disüibution of inheritance after death which is Faraid compared to make early planning such as disüibution by Hibah and Wasiyyah (Abdul Rashid & Yaakub, 2008). For them, writing a will or Wasiyyah is unnecessary because already have Faraid. More worst is Amanah Raya Berhad reported that RM315 millions of inheritance is not claimed by the heirs. This is because the heirs fails to be detected due to incomplete information, the heirs fighting between them and bring case to court, the heirs refuse to claim inheritance because the value is less and the customer of Amanah Raya Berhad does not leave the Wasiyyah that reported by MToday News Sdn (Ghul, Yahya, & Abdullah, 2014; Alma'amun, 2010) Bhd, 2017 in online newspaper.Thus, the research revealed that knowledge and perception have significant relationship with practice of Wasiyyah among Malay society and attitude do not have significant relationship.